Electron correlation in real time - Sansone, Giuseppe; Pfeifer, Thomas; Kuleff, Alexander I. (ChemPhysChem, 2012)
Abstract: Electron correlation, caused by the interaction among electrons in a multielectron system, manifests itself in all states of matter. A complete theoretical description of interacting electrons is challenging; different approximations have been developed to describe the fundamental aspects of the correlation that drives the evolution of simple (few‐electron systems in atoms/molecules) as well as complex (multielectron wave functions in atoms, molecules, and solids) systems. Electron correlation plays a key role in the relaxation mechanisms that characterize excited states of neutral or ionized atoms and molecules populated by absorption of extreme ultraviolet (XUV) or X‐ray radiation. The dynamics of these states can lead to different processes such as Fano resonance and Auger decay in atoms or interatomic Coulombic decay or charge migration in molecules and clusters. Many of these relaxation mechanisms are ubiquitous in nature and characterize the interaction of complex systems, such as biomolecules, adsorbates on surfaces, and hydrogen‐bonded clusters, with XUV light. These mechanisms evolve typically on the femtosecond (1 fs=10−15 s) or sub‐femtosecond timescale. The experimental availability of few‐femtosecond and attosecond (1 as=10−18 s) XUV pulses achieved in the last 10 years offers, for the first time, the opportunity to excite and probe in time these dynamics giving the possibility to trace and control multielectron processes. The generation of ultrashort XUV radiation has triggered the development and application of spectroscopy techniques that can achieve time resolution well into the attosecond domain, thereby offering information on the correlated electronic motion and on the correlation between electron and nuclear motion. A deeper understanding of how electron correlation works could have a large impact in several research fields, such as biochemistry and biology, and trigger important developments in the design and optimization of electronic devices.
First published: 08 December 2011
Gesehen am 22.08.2018